2015
DOI: 10.1016/j.amsu.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraceptives and venous thromboembolism: Are inflammatory bowel disease patients at increased risk? A retrospective study on a prospective database

Abstract: Recent studies showed an increased risk of venous thromboembolism (VTE) in patients receiving oral hormonal contraceptives. Inflammatory bowel diseases (IBD) often affect young patients and represent a pro-coagulant condition. This could result from active inflammation, but a potential role for genetic and molecular factors has been suggested. Hormonal contraceptives have also been associated with increased risk of VTE and the risk may be greater in IBD patients that already are in a pro-coagulant status, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…The average age of the participants was as 44.59 ± 10.18 years. In three studies sample age was reported as a range ( 33 , 34 , 43 ), and four studies did not report the descriptive information concerning the age of their sample ( 22 , 26 , 32 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…The average age of the participants was as 44.59 ± 10.18 years. In three studies sample age was reported as a range ( 33 , 34 , 43 ), and four studies did not report the descriptive information concerning the age of their sample ( 22 , 26 , 32 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective study, oestrogen-based contraceptives were not associated with an additional risk for thromboembolism in women with IBD in remission when compared to controls. 32 As IBD is considered a thrombophilic condition, particularly when disease is active, 33 Contraceptive Use in 2016. 34 This document placed the use of combined hormonal therapy in IBD into a 'grey area', as they are generally regarded as safe except for women with an increased risk of venous thromboembolism, in whom the risks may outweigh the benefits.…”
Section: Contraception In Ibdmentioning
confidence: 99%
“…The risk for VTE in the general population is higher in those with OCP use compared to those without OCP use [14]. Pellino, et al conducted a retrospective review of an Italian IBD database and compared 146 IBD patients on OCP to 290 non-IBD matched controls [15]. They found no significant difference in the incidence of VTE between IBD patients in remission and in non-IBD patients [15].…”
Section: Oral Contraceptive Use and Ibdmentioning
confidence: 99%
“…Pellino, et al conducted a retrospective review of an Italian IBD database and compared 146 IBD patients on OCP to 290 non-IBD matched controls [15]. They found no significant difference in the incidence of VTE between IBD patients in remission and in non-IBD patients [15]. In general, there is likely little avoidance of estrogen-based contraception in usual clinical practice [16,17].…”
Section: Oral Contraceptive Use and Ibdmentioning
confidence: 99%